(untitled) (Fiep Bulletin - online, 2011)
University Extension has become an academic practice at public universities in Brazil, UERJ and participates actively in this process. This article seeks to make an approach on the extension activities undertaken at the Institute of Physical Education and Sports of UERJ using the Rhythmic Gymnastics as an anchor, a constant process of social inclusion, cultural and educational community outside. Among the many goals that the activities of Extension can attend, we highlight those that most clearly, explain the academic and social commitment of the University. Extension activities should give special attention to the opportunities they offer to students for reflection and action around issues of Physical Education in constant tune with the real needs and interests of the communities in which they are contextualized. Thus, it is important that the activities that establish as clearly as possible the limits of field experience to enable participants to clearly identify the objectives of the activity, encouraging results achieved. The "Rhythmic Gymnastics Center" linked to the Project LAMGRES - Multidisciplinary Laboratory of Rhythmic Gymnastics with a focus on education and health, for fleshing out the various activities of the discipline / sport in our University is an interaction between the external and internal communities. Among these activities include the School Meeting Rhythmic Gymnastics IEFD / UERJ in its 21st edition, lectures with workshops, seminars, clinics, mini-courses and presenting work at scientific and academic events internal and external.